Using Applied Theater in Primary, Secondary, and Tertiary Prevention of Intimate Partner Violence: A Systematic Review. (January 2020) - Heard, Emma; Mutch, Allyson; Fitzgerald, Lisa
There is an immediate need to advance knowledge around the effective prevention of intimate partner violence (IPV), which is responsible for significant negative health and well-being outcomes for women around the world. Creative approaches are being explored internationally—this systematic review provides a timely synthesis of applied theater interventions addressing primary, secondary, and tertiary IPV prevention. Six hundred and ten articles were identified through a comprehensive search of five cross-disciplinary databases. Eleven studies discussed in 15 quantitative and qualitative peer-reviewed articles and one book chapter met the inclusion criteria and were included in the review. Articles were appraised using a standardized quality assessment tool and were analyzed within the context of IPV prevention. Of the reviewed studies, five were classified as primary prevention, four secondary, and two focused on tertiary prevention. Specific strategies used by each of the studies included healthy relationship training, rising awareness and community advocacy, service provider training, bystander training, and working with survivors. While the paucity and quality of current literature make it difficult to determine overall efficacy, this review points to the potential of applied theater as a useful prevention strategy, particularly when interactive, participatory methods are incorporated. Further, applied theater could be an effective tool for working in culturally diverse settings as well as with minority groups. Future applied theater program planning needs to include comprehensive evaluation. More rigorous investigation, involving mixed-method research approaches, is required to fully understand the potential of applied theater as a tool in the context of IPV prevention.